2013
DOI: 10.1186/1465-9921-14-67
|View full text |Cite
|
Sign up to set email alerts
|

The role of uPAR in epithelial-mesenchymal transition in small airway epithelium of patients with chronic obstructive pulmonary disease

Abstract: BackgroundEpithelial-mesenchymal transition (EMT) plays a crucial role in small airway fibrosis of patients with chronic obstructive pulmonary disease (COPD). Increasing evidence suggests that the urokinase plasminogen activator receptor (uPAR) is involved in the pathogenesis of COPD. Increased uPAR expression has been implicated in the promotion of EMT in numerous cancers; however the role of uPAR in EMT in small airway epithelial cells of patients with COPD remains unclear. In this study, we investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
86
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 39 publications
8
86
0
Order By: Relevance
“…Our data demonstrated the downregulation of E-cadherin and upregulation of vimentin in small airway epithelium of the COPD lungs, indicating the active EMT in small airways of COPD patients. These results are consistent with previous findings that EMT contributed to remodelling of small airways in COPD (3,30,31). Up to date, there are limited data regarding the potential role of FXR in EMT.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our data demonstrated the downregulation of E-cadherin and upregulation of vimentin in small airway epithelium of the COPD lungs, indicating the active EMT in small airways of COPD patients. These results are consistent with previous findings that EMT contributed to remodelling of small airways in COPD (3,30,31). Up to date, there are limited data regarding the potential role of FXR in EMT.…”
Section: Discussionsupporting
confidence: 83%
“…However, airway remodelling in COPD, such as peribronchiolar fibrosis, is mainly located in small airways. Furthermore, the large and small airways have different anatomical and pathophysiological characteristics (30). Therefore, the role of active EMT in small airways remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…27 We have recently shown that increased uPAR expression in the small airway epithelium of COPD patients participates in an active EMT process modulated by PI3K/ Akt and GSK3b. 17 uPAR is a glycosyl phosphatidylinositolanchored protein with a high affinity to uPA. The uPAR expression and its ability to bind uPA are required for signaling.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with our previous reports in intracellular that uPAR is increasing in CSE-induced cells. 17 …”
Section: Increased Upa Expression In Cse-induced Hsaepic Cellsmentioning
confidence: 99%
See 1 more Smart Citation